Bronchobiliary Fistula Following Laparoscopic Cholecystectomy - Than Than Aye; Htun Oo (Myanmar Medical Journal, 2025)
References 1. Li T-Y, Zhang Z-B. Congenital bronchobiliary fistula: A case report and review of the literature. World J Clin Cases. 2019 April; 7 (7): 881-890. doi: 10.12998/wjcc. v7.i7.881. 2. Mardani P, Kamran H, Khosravi F, Shahriarirad R, Shahabinejad P, Geramizadeh B, Soleimani N, Amirian A. Bronchobiliary fistulae as a complication of untreated pulmonary hydatid cyst presenting with bilioptysis: a report of two cases. Clin Case Rep. 2023 June; 11 (6): e7524. doi: 10.1002/ccr3.7524. 3. Mandal A, Sen S, Baig SJ. Bronchobiliary fistula. J Minim Access Surg. 2008 Oct- Dec; 4 (4): 111-113. doi: 10.4103/0972-9941.45208. 4. Yoon DH, Shim JH, Lee WJ, Kim PN, Shin JH, Kim KM. Percutaneous management of a bronchobiliary fistula after radiofrequency ablation in a patient with hepato- cellular carcinoma. Korean J Radiol. 2009 June; 10 (4): 411-415. doi: 10.3348/ kjr.2009.10.4.411. 5. Achalla LSV, Shinde RK, Jogdand SD, Anand A, Vodithala S. Biliary stent obstruction leading to bronchobiliary fistula: a rare case report. Cureus. 2022 July; 14 (7): e26514. doi: 10.7759/cureus.26514. 6. Lee J, Jung SM, Lee Y, Kim S-Y. Anaesthetic management for a patient with broncho- biliary fistula after pancreaticoduodenectomy: a case report. Medicine (Baltimore). 2019 May; 98 (19): e15694. doi: 10.1097/MD.0000000000015694. 7. Lazarou V, Moris D, Papalampros A, Tsilimigras DI, Karachaliou G-S, Petrou A. Bronchobiliary fistula after hepatectomy: a case report and review of the literature. Mol Clin Oncol. 2019 Oct; 11 (6): 602-606. doi: 10.3892/mco.2019.1935. 8. Zhou T, Wu W, Cheng C, Wang H, Hu X, Jiang Z. Bronchobiliary fistula after traumatic liver rupture: a case report. J Med Case Rep. 2024 June; 18 (1): 289. doi: 10.1186/ s13256-024-04620-1. 9. Gautam V, Kumar V, Agarwal S, Gupta S. Delayed diagnosis of bronchobiliary fistula complicating a paediatric living donor liver transplantation: a case report. Korean J Transplant. 2023 Dec; 37 (4): 293-298. doi: 10.4285/kjt.23.0044. 10. Health and Social Care Information Centre. Hospital Episode Statistics, Admitted Patient Care – England, 2011-12: Main operations, 3 characters table [Internet]. Leeds (UK): Health and Social Care Information Centre; 2013 [cited 2025 June 29]. https://digital.nhs.uk/data-and-information/publications/statistical/hospital- admitted-patient-care-activity/hospital-episode-statistics-admitted-patient-care- england-2011-12. 11. Bhati CS, Tamijmarane A, Bramhall SR. A tale of three spilled gallstones: one liver mass and two abscesses. Dig Surg. 2006; 23 (3): 198-200. doi: 10.1159/000094739. 12. Yadav RK, Yadav VS, Garg P, et al. Gallstone expectoration following laparoscopic cholecystectomy. Indian J Chest Dis Allied Sci. 2002 April-June; 44 (2): 133-135. 13. Frola C, Cannici F, Cantoni S, et al. Peritoneal abscess formation as a late complication of gallstones spilled during laparoscopic cholecystectomy. Br J Radiol. 1999 Feb; 72 (854): 201-203. doi: 10.1259/bjr.72.854.10365074. 14. Hand AA, Self ML, Dunn E. Abdominal wall abscess formation two years after laparoscopic cholecystectomy. Journal of the Society of Laparoscopic & Robotic Surgeons (JSLS). 2006 Jan-Mar; 10 (1): 105-107. 15. Chowbey PK, Bagchi N, Sharma A, et al. Abdominal wall sinus: an unusual present- ation of spilled gallstone. J Laparoendosc Adv Surg Tech A. 2006 Dec; 16 (6): 613- 615. doi: 10.1089/lap.2006.16.613. 16. Helme S, Samdani T, Sinha P. Complications of spilled gallstones following laparo- scopic cholecystectomy: a case report and literature overview. J Med Case Rep. 2009 July; 3: 8626. doi: 10.4076/1752-1947-3-8626. 17. Stevens JL, Laliotis A, Gould SWT. Hepatocolonic fistula: a rare consequence of retained gallstones after laparoscopic cholecystectomy. Ann R Coll Surg Engl. 2013 Nov; 95 (8): e139-e141. doi: 10.1308/003588413X13629960048550. 18. Zhang Q, Wang X, Yan C, Mu Y, Li P. Gallstone ectopia in the lungs: case report and literature review. Int J Clin Exp Med. 2014 Nov; 7 (11): 4530-4533. 19. Eryigit H, Oztas S, Urek S, Olgac G, Kurutepe M, Kutlu CA. Management of acqui- red bronchobiliary fistula: 3 case reports and a literature review. Journal of Cardiothoracic Surgery. 2007 Dec; 2: 52. doi: 10.1186/1749-8090-2-52. 20. Thompson J, Pisano E, Warshauer D. Cholelithoptysis: an unusual complication of laparoscopic cholecystectomy. Clin Imaging. 1995 Apr-Jun; 19 (2): 118-121. doi: 10.1016/0899-7071(94)00038-e. 21. Breslin AB, Wadhwa V. Cholelithoptysis: a rare complication of laparoscopic cholecystectomy. Med J Aust. 1996 Oct; 165 (7): 373-374. doi: 10.5694/j.1326- 5377.1996.tb125021.x. 22. Ramamurthy NK, Rudralingam V, Martin DF, et al. Out of sight but kept in mind: complications and imitations of dropped gallstones. Am J Roentgenol (AJR), 2013 June; 200 (6): 1244-1253. doi: 10.2214/AJR.12.9430. 23. Harnoss JM, Yung R, Brodsky RA, et al. Bronchobiliary fistula and lithoptysis after endoscopic retrograde cholangiopancreatography and liver biopsy in a patient with paroxysmal nocturnal haemoglobinuria. Am J Respir Crit Care Med. 2013 Feb; 187 (4): 451-454. doi: 10.1164/ajrccm.187.4.451a. 24. Karabulut N, Cakmak V, Kiter G. Confident diagnosis of bronchobiliary fistula using contrast-enhanced magnetic resonance cholangiography. Korean J Radiol. 2010 July-August; 11 (4): 493-496. doi: 10.3348/kjr.2010.11.4.493. 25. Katsinelos P, Paroutoglou G, Chatzimavroudis G, Beltsis A, Mimidis K, Katsinelos T, et al. Successful treatment of intractable bronchobiliary fistula using long-term biliary stenting. Surg Laparosc Endosc Percutan Tech. 2007 June; 17 (3): 206-209. doi: 10.1097/SLE.0b013e318058822d. 26. Guruvaiah N, Ponnatapura J. Bronchobiliary fistula: a rare postoperative compli- cation of spilled gallstones from laparoscopic cholecystectomy. BMJ Case Rep. 2021 July; 14 (7): e243198. doi: 10.1136/bcr-2021-243198. 27. Chua HK, Allen MS, Deschamps C, Miller DL, Pairolero PC. Bronchobiliary fistula: principles of management. The Annals of Thoracic Surgery, 2000 Oct; 70 (4): 1392- 1394. https://doi.org/10.1016/S0003-4975(00)01693-3.